Engineering Societies in the Agents World VIII - Artikis, Alexander (Springer, 2017)
This book constitutes the thoroughly refereed post-conference proceedings of the 7th International Workshop on Engineering Societies in the Agents World, ESAW 2007, held in Athens, Greece, in October 2007.